PENDAMPINGAN PENDIDIKAN HUKUM MENCEGAH AKSI PORNOGRAFI DI SMK PERINTIS 29 UNGARAN - Arista Candra Irawati; Wahyu Kristiningrum; Hani Irhamdessetya; Aniatul Khusna; Zhyka Sofhia Firdausi (Universitas Ngudi Waluyo, 2024)
The development of digital-based technology is getting faster and more sophisticated. The developments that occur have an impact on all aspects of human life, both in terms of social, economic, cultural and fulfillment of human life needs, opportunities and opportunities that are owned. Technological advances become information media that can be updated in seconds. Millennials utilize online media such as WhatsApp, Instagram, Telegram, and TikTok, the contents of which tend to be entertainment media but are often related to pornography. Cyber ​​pornography crimes are considered the spread of pornographic content via the internet. Through the Criminal Code, Law (UU) Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Furthermore, in Law Number 44 of 2008 concerning Pornography, regulations for the prevention and prosecution of Pornography crimes. Through this partnership activity, it is hoped that Class XII students who take part in legal education on preventing pornography as a healthy culture in everyday behavior. The importance of this education also increases knowledge of law enforcement in eradicating pornography crimes, which is poured into the form of devotion with the title: Legal Education Assistance to Prevent Pornographic Actions at SMK Perintis 29 Ungaran. In the implementation of this devotion activity, it is carried out using a participatory approach method, participants are required to actively participate in activities. The competencies that will be formed are marked by indicators of increasing knowledge and application of prevention of pornographic acts in behavior as a form of loving the Republic of Indonesia and preparing themselves to become a great generation of the nation. Abstrak Perkembangan teknologi berbasis digital semakin cepat dan canggih. Perkembangan yang terjadi berdampak terhadap segala aspek kehidupan manusia, baik dalam segi sosial, ekonomi, budaya maupun pemenuhan kebutuhan hidup manusia kesempatan dan peluang yang dimiliki. Kemajuan tekhnologi menjadi media informasi dapat terperbaharui dalam skala detik. Para kaum milenial memanfaatkan media-media online seperti whatsaap, instagram, telegram, dan tiktok, yang isi dalam media tersebut lebih cenderung sebagai media hiburan namun acapkali berkaitan dengan pornografi. Kejahatan Cyber pornography dinilai sebagai penyebaran muatan pornografi melalui internet. Melalui KUHP, Undang-undang (UU) Nomor 1 Tahun 2024 tentang Perubahan Kedua atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik. Selanjutnya dalam Undang-Undang Nomor 44 Tahun 2008 Tentang Pornografi regulasi pencegahan maupun penindakan kejahatan Pornografi. Melalui kegiatan kemitraan ini diharapkan, para Siswa Kelas XII yang mengikuti edukasi pendidikan hukum pencegahan aksi pornografi sebagai budaya sehat dalam perilaku sehari-hari. Pentingnya edukasi ini meningkatkan pula pengetahuan atas penegakkan hukum dalam memberantas tindak pidana pornografi, yang dituangkan Pengabdi ke dalam bentuk pengabdian dengan judul: Pendampingan Pendidikan Hukum Mencegah Aksi Pornografi Di SMK Perintis 29 Ungaran. Dalam pelaksanaan kegiatan pengabdian ini dilaksanakan dengan metode pendekatan partisipatif, para peserta dituntut aktif mengikuti kegiatan. Kompetensi yang akan dibentuk ditandai dengan indikator peningkatan pengetahuan dan penerapan pencegahan aktsi pornografi dalam perilaku sebagai wujud mencintai NKRI dan mempersiapkan diri menjadi generasi bangsa yang hebat.